FOXP3+ regulatory T cells in normal prostate tissue, postatrophic hyperplasia, prostatic intraepithelial neoplasia, and tumor histological lesions in men with and without prostate cancer. Issue 1 (6th November 2017) - Davidsson, Sabina; Andren, Ove; Ohlson, Anna‐Lena; Carlsson, Jessica; Andersson, Swen‐Olof; Giunchi, Francesca; Rider, Jennifer R.; Fiorentino, Michelangelo
Abstract : Background: The tumor promoting or counteracting effects of the immune response to cancer development are thought to be mediated to some extent by the infiltration of regulatory T cells (Tregs ). In the present study we evaluated the prevalence of Treg populations in stromal and epithelial compartments of normal, post atrophic hyperplasia (PAH), prostatic intraepithelial neoplasia (PIN), and tumor lesions in men with and without prostate cancer. Methods: Study subjects were 102 men consecutively diagnosed with localized prostate cancer undergoing radical prostatectomy and 38 men diagnosed with bladder cancer undergoing cystoprostatectomy without prostate cancer at the pathological examination. Whole mount sections from all patients were evaluated for the epithelial and stromal expression of CD4 + Tregs and CD8 + Tregs in normal, PAH, PIN, and tumor lesions. A Friedmańs test was used to investigate differences in the mean number of Tregs across histological lesions. Logistic regression was used to estimate crude and adjusted odds ratios (OR) for prostate cancer for each histological area. Results: In men with prostate cancer, similarly high numbers of stromal CD4 + Tregs were identified in PAH and tumor, but CD4 + Tregs were less common in PIN. Greater numbers of epithelial CD4+ Tregs in normal prostatic tissue were positively associated with both Gleason score and pT‐stage. We observed a fourfold increased risk of prostate cancer in men with epithelial CD4 + Tregs in the normal prostatic tissue counterpart. Conclusions: Our results may suggest a possible pathway through which PAH develops directly into prostate cancer in the presence of CD4 + Tregs and indicate that transformation of the anti‐tumor immune response may be initiated even before the primary tumor is established.